Screening for gestational diabetes mellitus and hyperglycemia in pregnancy with the glucose challenge test administered in early pregnancy. Issue 3 (11th December 2021) - Sfameni, Salvatore F.; Wein, Peter; Ngu, Andrew C. C.
Abstract: Objective: To determine the cut‐off value for the 75‐g glucose challenge test administered in early pregnancy to screen for gestational diabetes mellitus and abnormal carbohydrate metabolism in pregnancy. Methods: A prospective study involving 1500 antenatal patients attending a community hospital. Patients were screened with the 75‐g 1‐h glucose challenge test in early pregnancy and subsequently tested with the 75‐g 2‐h glucose tolerance test to diagnose gestational diabetes mellitus. Statistical methods were employed to determine the optimal plasma glucose cut‐off value for a positive result in early pregnancy. Results: A glucose challenge test value of 6.0 mmol/L (108 mg/dl) or more was selected as the preferred cut‐off level for further testing with a sensitivity of 83.5% (95% confidence interval [CI] 77.0%–88.9%) and specificity of 49.2% (95% CI 46.5%–52.0%). Conclusion: An early pregnancy glucose challenge test reading of 6.0 mmol/L (108 mg/dl) or more is effective in screening for gestational diabetes mellitus; a value of 10.0 mmol/L (180 mg/dl) or more is effective for finding pre‐pregnancy abnormalities of carbohydrate metabolism. The false‐positive glucose challenge test diagnoses gestational hyperglycemia, the treatment of which will improve perinatal outcome. Further testing based on risk factors will exclude a false‐negative glucose challenge test. A combination of universal early pregnancy screening and selective risk‐factor testing is recommended to detect the full range of abnormalities of carbohydrate metabolism encountered in pregnancy. Abstract : The glucose challenge test in early pregnancy is effective in screening for gestational diabetes mellitus and hyperglycemia in pregnancy.